Comparison of Acceptability Test of Alternative Diabetic Snacks Obtain from Fiber and Protein Levels Pineapple Moringa Velva with Addition of Oatmeal - Rihlah Sa'idah; Juliana Christyaningsih; Melina Sari; Patcharanee Pavadhgul (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Diabetes is a major public health problem. For diabetics, diet shows great potential in controlling blood glucose levels by practicing regular eating patterns, either snacking between meals. Then, it’s important to consume foods with a low glycemic index, meanwhile fulfill daily protein and fiber intake. This study aims to identify organoleptic tests, along with analysis of fiber and protein levels from the best organoleptic test results. This type of research was a pre-experimental design on 3 groups velva. Organoleptic tests were performed on 25 trained panelists using purposive sampling. Analysis technique uses kruskall wallis and mann whitney test. Also, laboratory tests for fiber and protein levels. The results of this study are diabetics have a daily calorie requirement of 1,500 kcal. Moreover, 150 kcal is required for one snack, 7.5 g of protein and 2.5 g for fiber is needed. In addition, based on the results of the organoleptic test, the best velva is formulation 3 (KN 03). The average value obtained from 25 panelists is 3.38. The fiber content contained in the formulation 3 velva is 3.19 g/100 g. Meanwhile, the protein content per 100 g is 8.68 g. The conclusion of this study is that diabetics can consume velva at a rate of 1 cup (100 g) with 151.9 kcal calories per snack consumption to meet 10% of their daily fiber and protein needs. The implication of this research is to find the best velva formulation with high fiber and protein levels for diabetics